Physical and chemical characterization of farinaceous product the central axis and pivot of jackfruit (Research, Society and Development, 2020)
Artocarpus heterophyllus Lam., popularly known as jackfruit, is native to India and widely disseminated in Brazil, mainly in the northeast region, due to favorable climatic conditions. Food products based on jackfruit flour are intended to complement the normal diet of the population, consisting of alternative sources of concentrated nutrients or other substances that have a beneficial nutritional or physiological effect on health, in simple or combined formulations. In this way, the objective of this work was to characterize physically and chemically the jackfruit residues (central axis and pivot) obtained by drying in an oven with air circulation at 60°C. The experiments were carried out at the Food Biochemistry and Biotechnology Laboratory at Federal University of Campina Grande. The physical and chemical characteristics determined were water content (%), fixed mineral residue (%), pH, crude protein (%) and total soluble solids (°Brix). The water content of the farinaceous product of the axis and pivot residues of the jackfruit was 5.81 and 11.59%, respectively, and pH of 5.73 and 5.67, respectively. The crude protein content of the axis flour was 3.72% and 6.12% for pivot flour. Axis and pivot farinaceous products showed physical and chemical characteristics within the established standards, demonstrating to be a product that can later be used in the formulation of new food products.